Protective effects of isolecanoric acid on neurodegenerative in vitro models. (February 2016) - de Pedro, Nuria; Cantizani, Juan; Ortiz-López, Francisco Javier; González-Menéndez, Victor; Cautain, Bastien; Rodríguez, Lorena; Bills, Gerald F.; Reyes, Fernando; Genilloud, Olga; Vicente, Francisca
Abstract: Parkinson's disease (PD) and Amyotrophic lateral sclerosis (ALS), are neurodegenerative disorders characterized by loss of dopaminergic or motor neurons, respectively. Although understanding of the PD and ALS pathogenesis remains incomplete, increasing evidence from human and animal studies has suggested that aberrant GSK3β, oxidative stress and mitochondrial damage are involved in their pathogenesis. Using two different molecular models, treatment with L-BMAA for ALS and rotenone for PD the effect of isolecanoric acid, a natural product isolated from a fungal culture, was evaluated. Pre-treatment with this molecule caused inhibition of GSK3β and CK1, and a decrease in oxidative stress, mitochondrial damage, apoptosis and cell death. Taken together, these results indicated that isolecanoric acid might have a protective effect against the development of these neurodegenerative disorders. Highlights: Parkinson's disease (PD) and Amyotrophic lateral sclerosis (ALS). Aberrant GSK3β, oxidative stress and mitochondrial damage. Isolecanoric acid, caused inhibition of GSK3β, decrease oxidative stress. Isolecanoric acid decreased mitochondrial damage, apoptosis and cell death. Isolecanoric acid might have a protective neurodegenerative effect.